Praktik Retribusi Pasar ditinjau dari Fiqih Muamalah - Deviyanti & Syafri Gunawan & Ahmatnijar (Jurnal El-Thawalib, 2020)
The market is part of the distribution that functions to distribute or deliver goods from producers to consumers through traders. The government has an important role in realizing an Islamic market. Market failure is also the background of the need for the government to play a role in the economy. Traders trading their goods to consumers are usually quoted or asked for rental fees by market officers, where the rental fee for the lapak is collected once a week or it can be said every week, the quotation for the stalls is Rp. 5000. However, in the applicable regional regulations For lapak levies traders are only given a rate of Rp. 1000, but in reality the traders pay Rp. 2000 for market officers, Rp. 2000 for security and cleaning and Rp. 1000 for retribution. The type of research used in this research is field research, namely the preparation will go directly to the field to research a problem, the data used are primary and secondary data, data collection methods are literature study methods, documentation, interviews and direct observation.  The results of this study indicate that the practice of retribution in Muara Sipongi Market that traders pay or are withdrawn monthly rent, namely Rp. 47,000, - and per day pay Rp. 5000. Then, there is a service fee for market officers as much as Rp. 2000 and and Rp. 1000 for retribution, as much as Rp. 2000 for cleaning and security services by market officers. the market clerk gives a receipt as proof of payment to the merchant. The Fiqh Muamalah review is that according to the pillars it has been fulfilled, but in terms of the conditions it has not been fulfilled where traders feel disappointed in paying stalls for security and cleaning services, even though the initial contract was not notified by market officers.